Management of Complex Risk of the Airline's Activities in order to Ensure Economic Security - Anna A. Burdina (UIKTEN, 2021)
The study proposes to consider the concept of complex risk of an airline from the position of a systematic approach and define risk as a threat to the economic security of an airline. The analysis of theoretical and methodological aspects of risk assessment is carried out. One method is proposed for determining and predicting a complex risk as a threat to the economic security of an airline based on an analysis of the probability of events and the impact on the company's activities in order to make effective management decisions to strengthen the economic security of an airline.